2003
DOI: 10.1159/000074905
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine Production, Lymphocyte Proliferation and T-Cell Receptor Vβ Expression in Primary Peripheral Blood Mononuclear Cell Cultures from Nickel-Allergic Individuals

Abstract: Background: Clinical history and patch test constitute the two cornerstones in the diagnosis of nickel (Ni) allergy. Due to technical and interpretative limits of the patch test, the in vitro lymphocyte transformation test (LTT) has been developed for confirming contact allergy; however, most studies show an overlap in lymphocyte proliferation between Ni-allergic and nonallergic subjects using the LTT. The aim of this study was to see if the secretion of cytokines, especially interleukin (IL)-10 and IL-17, or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
40
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 23 publications
4
40
0
Order By: Relevance
“…Neither of the studies above included analysis of regulatory [IL-10 and/or transforming growth factor-b (TGF-b)] cytokines, but other studies have compared regulatory, Th1-and Th2-type cytokines by ELISA. Cederbrant et al [16] using a very limited number of subjects demonstrated Ni 2þ -induced IL-10 levels in allergic subjects whereas IFN-g levels did not differ between PBMC from allergic and PBMC from control subjects, and IL-4 could not be detected. In contrast, Rustemeyer et al [19] based on a larger study population found a higher number of allergic subjects responding with IL-5 and IFN-g, although IFN-g could only be detected if PBMC were costimulated with IL-12.…”
Section: Discussionmentioning
confidence: 95%
“…Neither of the studies above included analysis of regulatory [IL-10 and/or transforming growth factor-b (TGF-b)] cytokines, but other studies have compared regulatory, Th1-and Th2-type cytokines by ELISA. Cederbrant et al [16] using a very limited number of subjects demonstrated Ni 2þ -induced IL-10 levels in allergic subjects whereas IFN-g levels did not differ between PBMC from allergic and PBMC from control subjects, and IL-4 could not be detected. In contrast, Rustemeyer et al [19] based on a larger study population found a higher number of allergic subjects responding with IL-5 and IFN-g, although IFN-g could only be detected if PBMC were costimulated with IL-12.…”
Section: Discussionmentioning
confidence: 95%
“…The immunological (delayed-type hypersensitivity) response following re-exposure to Ni is mainly T-cell mediated [4][5][6]. Analyses of cytokine production by Ni-specific T cells have demonstrated a mixed Th1-and Th2-type cytokine profile in both T-cell clones and peripheral blood mononuclear cells (PBMC) [7][8][9][10][11]. Analyses of Ni-specific T-cell clones generated from PBMC and skin of allergic patients have suggested that both CD4 + and CD8 + T cells are involved in the immune response to Ni [12,13] whereas analysis of PBMC from Niallergic subjects have primarily identified Ni-specific CD4 + T cells [10,14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Analyses of cytokine production by Ni-specific T cells have demonstrated a mixed Th1-and Th2-type cytokine profile in both T-cell clones and peripheral blood mononuclear cells (PBMC) [7][8][9][10][11]. Analyses of Ni-specific T-cell clones generated from PBMC and skin of allergic patients have suggested that both CD4 + and CD8 + T cells are involved in the immune response to Ni [12,13] whereas analysis of PBMC from Niallergic subjects have primarily identified Ni-specific CD4 + T cells [10,14,15]. We [16] and others [10] have reported production of significant levels of the immuno-regulatory cytokine IL-10 following Ni stimulation of PBMC from Niallergic subjects compared to healthy controls in vitro whereas another study [17] suggested Ni-induced IL-10 production primarily in PBMC from Ni tolerized subjects.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A protective oxide layer is typically generated on these alloys acting as a barrier against chemical attack and corrosion, although this oxide layer can be depleted by wear, corrosion or fatigue. These processes produce the release of ions or wear debris which may cause some allergic reaction and biocompatibility problems [3][4][5] . For instance, the low wear resistance of Ti6Al4V alloy has been demonstrated to induce the release of aluminium (Al) and vanadium (V) ions which are potentially hazardous for human body 6 .…”
Section: Introductionmentioning
confidence: 99%